The Ismailis in the Middle Ages a history of survival, a search for salvation - Virani, Shafique N. (Oxford [u.a.] Oxford University Press, 2007)
Introduction -- Recovering a lost history -- The eagle returns -- Veiling the sun -- Summoning to the truth -- Possessors of the command -- Qibla of the world -- The way of the seeker -- Salvation and imamate -- Conclusion
Introduction -- Recovering a lost history -- The eagle returns -- Veiling the sun -- Summoning to the truth -- Possessors of the command -- Qibla of the world -- The way of the seeker -- Salvation and imamate -- Conclusion
Includes bibliographical references (p. 265-289) and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Ismailites -- History; Geschichte; Ismailites -- History